Enhancing engineering education in electric drive systems through integrated computer simulation modules - Baharom, Rahimi; Hashim, Norazlan; Hannoon, Naeem M. S.; Rahman, Nor Farahaida Abdul (Institute of Advanced Engineering and Science, 2025)
The integration of computer simulation modules in electric drive courses plays a pivotal role in modern engineering education by offering students hands-on experience and fostering a deeper understanding of theoretical concepts. This study highlights the significance of enhancing engineering education through an innovative simulation module designed to analyze electric drive systems. The module enables the specification of suitable converters and machines for speed and position control systems while focusing on the steady-state operations of AC and DC drives. Through simulation exercises, students explore converter circuit topologies, control strategies, and the two-quadrant operations of electric machines using fully controlled two-pulse bridge circuits, encompassing motoring and braking modes in the first and fourth quadrants. The proposed module demonstrates its effectiveness in bridging theory and practice, evidenced by significant improvements in students' comprehension of circuit configurations and control algorithms. The approach enhances critical thinking, problem-solving skills, and the ability to relate theoretical knowledge to practical applications. Future research will focus on extending the module's capabilities to incorporate additional quadrants of operation and advanced control strategies. By integrating such tools into the curriculum, educators can better prepare students for the evolving demands of engineering careers.